Religious Moderation as Lived Practice among Islamic Education Students - Mansur Mansur; M Iqbal Nasir; Harmila Yunus (JURNAL ISLAM NUSANTARA, 2025)
This study aims to examine how religious moderation is understood, developed, and strengthened among students of Islamic Education in an Islamic higher education context. In recent years, religious moderation has become a crucial societal issue amid rising polarization, radical narratives, and identity-based tensions within multicultural societies. Islamic universities are therefore challenged to translate normative discourses of moderation into lived educational practices that shape students’ cognition, attitudes, and behavior. This qualitative study employed a phenomenological approach, using in-depth interviews, participant observation, and document analysis. Data were analyzed through data condensation, display, and verification to capture the essence of participants’ lived experiences. The findings reveal that students conceptualize religious moderation as a balanced integration of national commitment, respect for diversity, anti-violent principles, and openness to local culture. Academic factors, including curriculum integration, reflective pedagogy, and lecturers’ role modeling, significantly influence the internalization of moderation values. Non-academic activities such as interfaith dialogue, mentoring, community service, and pesantren-based programs further reinforce these values. Institutionally, structured courses, competent lecturers, and praxis-oriented strategies function as preventive mechanisms against radicalism. This study contributes theoretically by framing religious moderation as lived practice rather than mere doctrine and recommends strengthening integrative, context-sensitive strategies in Islamic higher education.